Soft Computing in Materials Development and its Sustainability in the Manufacturing Sector. - Patnaik, Amar.; Kukshal, Vikas; Agarwal, Pankaj; Sharma, Ankush; Choudhary, Mahavir ([Place of publication not identified] : CRC Press, 2022)
This book focuses on the application of soft computing in materials and manufacturing sectors with the objective to offer an intelligent approach to improve the manufacturing process, material selection and characterization techniques for developing advanced new materials. It unveils different models and soft computing techniques applicable in the field of advanced materials and solves the problems to help the industry and scientists to develop sustainable materials for all purposes. The book focuses on the overall well-being of the environment for better sustenance and livelihood. Firstly, the authors discuss the implementation of soft computing in the various areas of engineering materials. They also review the latest intelligent technologies and algorithms related to the state-of-the-art methodologies of monitoring and effective implementation of sustainable engineering practices. Finally the authors examine the future generation of sustainable and intelligent monitoring techniques beneficial for manufacturing, and cover novel soft computing techniques for the purpose of effective manufacturing processes at par with the standards laid down by the International Standards of Organization (ISO). This book is intended for academics and researchers from all the fields of engineering interested in joining interdisciplinary initiatives on soft computing techniques for advanced materials and manufacturing.
1. Predictive Maintenance of Industrial Rotating Equipment Using Supervised Machine-Learning. Hare Shankar Kumhar, Kumari Sarita, Vikas Kukshal, Sanjeev Kumar2. Predictive Approach on Creep life of N-Based single crystal superalloy using Optimized Machine Learning Regression Algorithms. Vinay Polimetla, Srinu Gangolu3. Artificial Neural Networks based real-time modelling while Milling Aluminium 6061 alloy. Shaswat Garg, Satwik Dudeja, Navriti Gupta4. Smart Techniques of Microscopic Image Analysis and Real Time Temperature Dispersal Measurement for Quality Weld Joints. Rajesh V. Patil, Abhishek M. Thote5. Industrial Informatics Cache Memory Design for Single Bit Architecture for IoT Approaches.Reeya Agrawal, Neetu Faujdar6. The Bending Behaviour of Carbon Fiber Reinforced Polymer Composite for Car Roof Panel using ANSYS 21. Mohd Faizan, Swati Gangwar7. Sustainable Spare Parts Inventory and Cost Control Management using AHP based Multi Criterion Framework: Perspective to Petroleum & Fertilizer Industries.Sandeep Sharda, Sanjeev Mishra8. Simulation of Deployment of Inflatable Structures through Uniform Pressure Method. Aquib Ahmad Siddiqui, V. Murari9. Experimental and Machine Learning Approach to Evaluate the Performance of Refrigerator and Air Conditioning using TiO2 nano-Particle. Harinarayan sharma, Aniket kumar Dutt, Pawan kumar, Mamookho Elizabeth Makhatha10. Numerical and Experimental Investigation on Thinning in Single Point Incremental Sheet Forming (SPIF). Sahil Bendure, Rahul Jagtap, Malaykumar Patel11. Smart Manufacturing: Opportunities and Challenges overcome by Industry 4.0. Ishan Mishra, Sneham Kumar, N Gupta12. Multi-Response Optimization of Process Parameters in End Milling of Lm24/B4c Metal Matrix Composite Using TOPSIS Algorithm. A. Singhai, K. Dhakar, P.K. Gupta13. Numerical and experimental investigation of additive manufactured cellular lattice structures. V Phanindra Bogu, Locherla Daloji, Bangaru babu Popuri14. Wear measurement by real time condition monitoring using ferrography. Swati Kamble, Rajiv B15. Design, Modelling and Comparative Analysis of a Horizontal Axis Wind Turbine. Ninad Vaidya, Shivprakash B. Barve
OCLC-licensed vendor bibliographic record.
Keywords: Soft computing; COMPUTERS / Machine Theory; TECHNOLOGY / Electricity; TECHNOLOGY / Manufacturing